DRAMAS OF DUSAN KOVACEVIC IN COURSE OF SERBIAN LANGUAGE AND LITERATURE (Heritage, 2021)
In the paper, we will deal with literary knowledge and reading competencies of a student which are necessary for a coherent literary and methodically based interpretation and evaluation of the genre in contemporary literature teaching on the example of three dramas by Dusan Kovacevic: Claustrophobic Comedy, Professional and Hilarious Tragedy. The purpose of the paper is to show how complex and significant the reading of a dramatic text can be, and perhaps unfairly neglected in teaching practice, given how important it is to research and define the literary knowledge and competencies that are necessary for the student to acquire by reading and studying the genre and reach the level of creative reaction to it. The purpose of the paper is to point out the linguistic and stylistic characteristics and theoretical basis of the drama from the corpus of research, which would methodically justified give the possibility of their incorporation into the high school curriculum.
Keywords: literature, language, methodology, drama, genre, Dusan Kovacevic, Claustrophobic Comedy, Professional, Hilarious Tragedy